2018
DOI: 10.2196/jmir.8850
|View full text |Cite
|
Sign up to set email alerts
|

Web-Delivered Cognitive Behavioral Therapy for Distressed Cancer Patients: Randomized Controlled Trial

Abstract: BackgroundWeb-based interventions present a potentially cost-effective approach to supporting self-management for cancer patients; however, further evidence for acceptability and effectiveness is needed.ObjectiveThe goal of our research was to assess the effectiveness of an individualized Web-based cognitive behavioral therapy (CBT) intervention on improving psychological and quality of life outcomes in cancer patients with elevated psychological distress.MethodsA total of 163 distressed cancer patients (111 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(100 citation statements)
references
References 36 publications
2
97
1
Order By: Relevance
“…Cancerspecific distress did not significantly moderate outcomes at any time point. Table 3 These outcomes add to the findings from three recent RCTs of online programs for recently diagnosed acute cancer survivors [19,15,18]. In contrast with the CancerCope trial for newly diagnosed distressed-patients [19], where no QOL impact was found, our study found FMW significantly improved emotional functioning.…”
Section: No Significant Differences Between Groups Were Observed For supporting
confidence: 71%
See 3 more Smart Citations
“…Cancerspecific distress did not significantly moderate outcomes at any time point. Table 3 These outcomes add to the findings from three recent RCTs of online programs for recently diagnosed acute cancer survivors [19,15,18]. In contrast with the CancerCope trial for newly diagnosed distressed-patients [19], where no QOL impact was found, our study found FMW significantly improved emotional functioning.…”
Section: No Significant Differences Between Groups Were Observed For supporting
confidence: 71%
“…Table 3 These outcomes add to the findings from three recent RCTs of online programs for recently diagnosed acute cancer survivors [19,15,18]. In contrast with the CancerCope trial for newly diagnosed distressed-patients [19], where no QOL impact was found, our study found FMW significantly improved emotional functioning. This QOL benefit differs somewhat from our pilot RCT where physical, rather than emotional, functioning was improved [15], and the STREAM program for newlydiagnosed patients [18], where all QOL domains except emotional functioning improved.…”
Section: No Significant Differences Between Groups Were Observed For supporting
confidence: 71%
See 2 more Smart Citations
“…As most readily accessible websites are information-based sites, further work is needed to understand how these resources can be designed to maximise their impact for users. Studies examining the impact of web-based therapeutic programmes to reduce distress or anxiety in cancer patients frequently incorporate strategies such as reminder emails, personalised content, goal setting, videos and homework to increase user engagement (Beatty, Koczwara, & Wade, 2016;Chambers et al, 2018;Wootten et al, 2015). Identifying mechanisms for incorporating these strategies into information-based programmes may help to increase user engagement and encourage repeat visits thereby helping to address information needs.…”
Section: Discussionmentioning
confidence: 99%